Governance and patient safety in the surgical area of a hospital - Orejuela Baquero, Diana Miley; López López, Maria Nela; González, María Fernanda (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Objective: To analyze the governance of the Patient Safety Policy in the health professionals of the surgical area of an ESE of the city of Cali in the year 2020. Methodology: Descriptive cross-sectional study, with a quantitative observational approach and deductive method. Results: 56.6% of the population is not aware of the patient safety policy, leading to a high risk of adverse events. Conclusions: The study population is unaware of the formal rules of the institutional patient safety policy; the mechanisms for dissemination and implementation of the policy should be improved.